Peningkatan Kualitas Produk dengan Metode QFD dan Seven Tools di Home Industry Tas Sidoarjo - Putri, Eka Adela; Titisari, Manik Ayu (Fakultas Teknik Universitas Tulang Bawang, 2026)
The home-based bag industry is one of the growing creative sectors, driven by rising demand for functional and aesthetic products. This study aims to improve product quality in a home-based bag business using an integrated approach combining Quality Function Deployment (QFD) and Seven tools. Conducted at X’s Bag Industry in Tanggulangin, Sidoarjo, the research began with collecting customer needs via a questionnaire based on Garvin’s eight quality dimensions. Data were tested for validity and reliability, then analyzed using the House of Quality (HoQ) to determine key technical attributes. The top priorities identified were raw material selection, stitching quality control, and product design, with the highest priority weight reaching 43.25. Quality issues were further examined using Seven tools, check sheets, histograms, Pareto and fishbone diagrams, revealing that 81.4% of total defects originated from just three main causes. Using the 5W+1H approach, practical improvement strategies were proposed. The study confirms that integrating QFD and Seven tools is effective for enhancing product quality in home industries. Keywords: House of quality, Product quality, QFD, Seven tools